Prevalence and risk factors of Helicobacter pylori infections in the patients suffering from acid-peptic disease at tertiary care center, Gujarat, India - Kukreja, Anjali K.; Pandya, Himani B.; Kumar, Santosh (International Journal of Advances in Medicine, 2018)
Background: Helicobacter pylori (H. pylori) infection is a medical encumber especially in the developing countries, ranging from acute inflammation to malignancy. The study is intended to explore the prevalence of H. pylori infection and also to compute its associated risk factors. Methods: Sixty two (n=62) symptomatic patients attending the tertiary care hospital, were included in the study. Two antral biopsies collected from each patient were subjected to rapid urease test and Gram staining. IgG antibodies were detected by rapid test based on the principle of Immunochromatography. To evaluate the risk factors, various determinants were asked to each patient in the form of questionnaire. Statistical analysis was done using Fisher exact test. P value < 0.05 was considered significant. Results: Prevalence rate of H. pylori infection was 24.19 % (15/62). More than half (53%) of the infected patients had complained of persistent burning abdominal pain. Prevalence rate was found highest in the patients suffering from peptic ulcer disease (66.6%, P=0.0237). Consumption of unfiltered water (P=0.007, Odd Ratio (OR)-1.06), eating spicy food, meat, fish and chili pepper (P=0.052, OR-1.01) was found the major risk factors. Addictive habits of either smoking/alcohol/tobacco (P=0.904) were not associated with infection. Conclusions: Prevalence of H. pylori infection was found low comparatively and was mainly associated with symptom of persistent burning abdominal pain and peptic ulcer. Use of unfiltered water, spicy food, chili pepper and meat undoubtedly increase the risk of acquiring H. pylori infection. Addictive habits were not significantly associated with infection.